Physical properties and biocompatibility effects of doping SiO2 and TiO2 into phosphate-based glass for bone tissue engineering. (August 2018) - Aldaadaa, Alaa; Al Qaysi, Mustafa; Georgiou, George; MA Leeson, Rachel; Knowles, Jonathan C
Phosphate glass is continuing to gain more attention as potential bone substitutes. The ternary (P2 O5 -CaO-Na2 O) is investigated in terms of both physical properties and biocompatibility by doping different percentages of SiO2 and TiO2 . Two groups were prepared; the first has different percentages of TiO2 and SiO2, whereas the second group compositions have 5 mol% TiO2 and 5 mol% SiO2 being added to compensate the network-forming oxide P2 O5 and the network-modifying oxide CaO. Density, mass loss, pH, DTA, XRD, and cation release experiments were performed to study the physicochemical properties of the compositions, while MG63 and hMS cells were used within in vitro cell culture to study their biocompatibility. Results showed that an increase in TiO2 content correlated with an increase in glass density, decreased mass loss, increased trend of Tg and Tm values, and Na + and Ca 2+ release in group 1. There was no improvement in the MG63 viability or the ability of hMSCs to differentiate into osteoblasts where TiO2 decreased in favour of SiO2 . Furthermore, in group 2, 50P2 O5 –25CaO was less dense than 45P2 O5 –30CaO, degraded dramatically less, had lower Tg and Tm values and released less Na + and Ca (2+) . The synergistic effect of doping 5 mol% TiO2 and 5 mol% SiO2 increased the MG63 viability in both compositions and was found 45P2 O5 –30CaO to have promising results in terms of the ability of hMSCs to differentiate into osteoblasts. To conclude, substituting TiO2 in place of SiO2 improved the physical properties and the biocompatibility of (P2 O5 -CaO-Na2 O) glass system, whereas doping 5 mol% SiO2 and 5 mol% TiO2 together in place of P2 O5 and CaO had a synergistic effect in controlling their degradation rate and improving their biological responses.